The next-generation X-ray galaxy survey with eROSITA. Issue 2 (11th August 2020) - Basu-Zych, Antara R; Hornschemeier, Ann E; Haberl, Frank; Vulic, Neven; Wilms, Jörn; Zezas, Andreas; Kovlakas, Konstantinos; Ptak, Andrew; Dauser, Thomas
ABSTRACT: eROSITA, launched on 2019 July 13, will be completing the first all-sky survey in the soft and medium X-ray band in nearly three decades. This 4-yr survey, finishing in late 2023, will present a rich legacy for the entire astrophysics community and complement upcoming multiwavelength surveys (with, e.g. the Large Synoptic Survey Telescope and the Dark Energy Survey). Besides the major scientific aim to study active galactic nuclei (AGNs) and galaxy clusters, eROSITA will contribute significantly to X-ray studies of normal (i.e. not AGN) galaxies. Starting from multiwavelength catalogues, we measure star formation rates and stellar masses for 60 212 galaxies constrained to distances of 50–200 Mpc. We chose this distance range to focus on the relatively unexplored volume outside the local Universe, where galaxies will be largely spatially unresolved and probe a range of X-ray luminosities that overlap with the low luminosity and/or highly obscured AGN population. We use the most recent X-ray scaling relations as well as the on-orbit eROSITA instrument performance to predict the X-ray emission from XRBs and diffuse hot gas and to perform both an analytic prediction and an end-to-end simulation using the mission simulation software, sixte . We consider potential contributions from hidden AGN and comment on the impact of normal galaxies on the measurement of the faint end of the AGN luminosity function. We predict that the eROSITA 4-yr survey, will detect ≳15 000 galaxies (3σ significance) at 50–200 Mpc, which is ∼100 × more normal galaxies than detected in any X-ray survey to date.